(untitled) (Journal of The Colloquium for Information Systems Security Education, 2020)
Improving the Pipeline is an NSF grant project [1] to extend the Information Assurance and Cybersecurity pipeline into the high school environment by offering an after-school for college credit course to students. This paper discusses the use of an isolated and portable Raspberry Pi network within the course.